Immune function analysis in a pediatric patient with a de novo ALPK1 gene mutation - Chuan, Xue; Ren, Aiyan; Hu, Shiyue; Li, Qian; Zhu, Yin; Zhang, Pingping; Wang, Lin; Du, Qing; Li, Hong; Chen, Yan; Huang, Pei; Du, Zuochen (Frontiers in Immunology, 2025)
IntroductionROSAH syndrome is a rare autosomal dominant disorder caused by heterozygous missense mutations in the ALPK1 gene. It is clinically characterized by a spectrum of manifestations, including retinal dystrophy, optic disc edema, splenomegaly, anhidrosis, and headaches. This study performed an integrated evaluation of clinical manifestations, genetic alterations, and immunological profiles in a pediatric ROSAH syndrome case harboring an ALPK1 mutation, with the objective of dissecting its putative immune-mediated pathogenesis.MethodsA 12-year-old male with unexplained splenomegaly and multisystem symptoms underwent clinical evaluation. Whole-exome and Sanger sequencing were used to identify ALPK1 variants. Western blotting was applied to assess the activation status of the NF-κB pathway in peripheral blood mononuclear cells (PBMCs), coupled with flow cytometric characterization of T- and B-lymphocyte subset distributions. Clinical manifestations and treatment of ROSAH Syndrome caused by ALPK1 mutations were summarized by literature review.ResultsThe individual presented with progressive visual loss, anhidrosis, migraine, and arthralgia. A heterozygous de novo ALPK1 variant (c.710C>T, p.Thr237Met) was identified. Elevated phosphorylated IKKβ levels indicated NF-κB pathway activation. Lymphocyte profiling demonstrated markedly diminished CD3+ and CD8+ T-cell counts, with the CD4+/CD8+ ratio escalating to 2.61, concurrently with elevated proportions of activated CD4+, CD8+ T cells, and regulatory T-cell populations. B-cell lineage anomalies featured expansions in transitional B-cell subsets and plasmablasts, paralleled by reduced serum immunoglobulin concentrations. Approximately 70 cases have been reported globally, linked to four ALPK1 mutations (c.710C>T, c.761A>G, c.830C>T, c.476C>T). Key clinical features include severe ocular involvement (retinal degeneration, optic nerve edema) and systemic manifestations such as splenomegaly and anhidrosis. Current management focuses on anti-inflammatory therapy and symptomatic support, while retinal degeneration remains untreatable.DiscussionThis case links a de novo ALPK1 mutation to constitutive NF-κB activation and immune dysfunction in ROSAH syndrome. Early genetic and immunological screening is essential for diagnosis and management of ROSAH syndrome. Targeted immunotherapy may alleviate symptoms, but further research is needed to define standardized approaches for this rare disorder.